EFFICACY OF SHUNTHI KALPA IN THE MANAGEMENT OF ATISARA (International Journal of Ayurveda and Pharma Research, 2016)
Diarrhea (Atisara) has long been recognized as an important health problem in all age groups and is a major cause of morbidity and mortality in rural communities of socio-economically backward and developing countries. According to Ayurveda Atisara means excessive flow of watery stool through anus. In the present study total 100 patients of Atisara were selected from Atisara from OPD and IPD unit of Dr. M. N. Agashe hospital, Satara. For the clinical study Shunthi Kalpa was selected as the trial drug which was given for the duration of 6 days in the dose of 2gm thrice a day. It was observed that 36% patients were from the age group 10-20 yrs, 68% were females, 56% were from lower socio economic class. Sama Jivha was found in all the patients and Jala Nimajjana Pariksha was positive in 96% patients. Among results Dravamalapravritti showed 96.36% relief, 94.44% improvement in Udarshula, 88.85% improvement in Agnimandya, 83.73% relief in Daurbalya and 78.66% improvement was seen in Aruchi.  All the symptoms showed highly significant results. 92% patients showed complete relief among which 60% were within first 3 days. Hence it can be concluded that Shunthi Kalpa is very effective remedy in the patients of Atisara having Amavastha.